2017
DOI: 10.18632/oncotarget.19587
|View full text |Cite
|
Sign up to set email alerts
|

Serum peptidome profiling for the diagnosis of colorectal cancer: discovery and validation in two independent cohorts

Abstract: Colorectal cancer (CRC) is one of the most common malignant neoplasms worldwide. Except for the existing fecal occult blood test, colonoscopy and sigmoidoscopy, no widely accepted in vitro diagnostic methods have been available. To identify potential peptide biomarkers for CRC, serum samples from a discovery cohort (100 CRC patients and 100 healthy controls) and an independent validation cohort (91 CRC patients and 91 healthy controls) were collected. Peptides were fractionated by weak cation exchange magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 63 publications
(69 reference statements)
2
14
0
Order By: Relevance
“…Experimentally, it was reported that complement C3 can be considered as an early diagnostic marker for some type of cancers [40,44,45]. The above described research supports the results of our metaanalysis from different angles, indicating that our analytical results are reliable.…”
Section: Discussionsupporting
confidence: 88%
“…Experimentally, it was reported that complement C3 can be considered as an early diagnostic marker for some type of cancers [40,44,45]. The above described research supports the results of our metaanalysis from different angles, indicating that our analytical results are reliable.…”
Section: Discussionsupporting
confidence: 88%
“…As in previous studies [ 27 , 28 , 43 ], all plasma samples were fractionated using weak cation exchange magnetic beads to gather and enrich the proteins or peptides, according to the instructions provided by the supplier (ClinProt™, Bruker Daltonics, Billerica, USA) [ 44 , 45 ]. The samples were purified and isolated through three steps: binding, washing, and elution.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma peptides, such as hormones, cytokines and growth factors, promote homeostasis in many biological processes [26]. Additionally, some plasma peptides have been found to be associated with age-related diseases, including Alzheimer's disease, hypertension, type 2 diabetes, and colorectal cancer [27][28][29][30][31]. Furthermore, our previous study shows that some peptides are highly correlated with chronological age in a Chinese population, such as fragment of apolipoprotein A-I, fibrinogen alpha, albumin and so on [19].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of these peptides was performed using LC-MS/MS. Notably; MALDI-TOF MS and LC-MS/MS were applied to analyze; diagnose human disease and identify potential biomarkers of health status using biosamples such as serum/plasma; saliva and urine [110].…”
Section: Expanding the Horizon For Mass Spectrometrymentioning
confidence: 99%